The bioactive peptide VLATSGPG regulates the abnormal lipid accumulation and inflammation induced by free fatty acids in HepG2 cells via the PERK signaling pathway. (May 2023) - Jin, Ritian; Juventus Aweya, Jude; Lin, Rong; Weng, Wuyin; Shang, Jiaqi; Wang, Dangfeng; Fan, Yiling; Yang, Shen
Graphical abstract: Highlights: VLATSGPG inhibits the activation of PERK. VLATSGPG reduces intracellular lipid accumulation. Cellular inflammation levels are inhibited by VLATSGPG. VLATSGPG inhibits the development of nonalcoholic fatty liver disease. Abstract: VLATSGPG (VLA) was a DPP-IV inhibitory peptide isolated from salmon ( Salmo Salar ) skin. Here, we demonstrated that VLA inhibited the activation of PERK through the AKT signaling pathway. Furthermore, we investigated the effect of VLA on free fatty acid (FFA)-induced lipid accumulation disorder and inflammation in HepG2 cells, elucidating the potential regulatory mechanism in this nonalcoholic fatty liver disease cell model. VLA reduced the mRNA expression of adipogenic factors FAS, ACC, and SCD-1 through the PERK/eIF2α pathway and the level of apolipoprotein B-100 secretion. These may contribute to the reducing FFA-induced lipid accumulation in cells and reducing intracellular lipid levels. In addition, VLA increased IκBα mRNA expression via the PERK/IκBα pathway, inhibited the NF-κB p65 activation, and thus inhibited cell inflammation.